Characterization of Salmonella adaptation in response to phage treatment in broiler chickens - Lorna Agapé; Pierrette Menanteau; Florent Kempf; Madeline Morinet; Marianne Nicolas; Olivier Boulesteix; Mickaël Riou; Isabelle Virlogeux-Payant; Catherine Schouler; Philippe Velge (Veterinary Research)
Abstract Salmonella constitutes a significant public health threat due to its widespread association with foodborne diseases, particularly those associated with contaminated poultry products. In this context, phage therapy has emerged as a promising strategy to control these infections. However, the natural emergence of phage-insensitive bacterial strains poses challenges for the efficacy of phage therapy. Understanding the adaptive response of Salmonella to phages in vivo is essential for developing effective therapeutic interventions. This study investigates the adaptive responses of Salmonella to phages-induced challenges, deciphers the underlying mechanisms and analyzes their in vivo consequences. Following repeated administrations of a six-phage cocktail in chickens, a panel of 145 random Salmonella isolates was recovered and characterized. Among these, 48% exhibited reduced sensitivity to a single phage from the phage cocktail, without evidence of cross-resistance; the vast majority of isolates remained susceptible to other phages. We identified two distinct bacterial adaptation profiles both associated with modifications in the lipopolysaccharide (LPS) structure, which appears as the phage receptor. The first profile displayed a complete resistance phenotype resulting in a rough-type Salmonella due to a genetic mutation in the rfbD gene involved in LPS biosynthesis. The second profile exhibited a transient and partial resistance phenotype, due to increased LPS glucosylation, likely associated to phase variation. This phenomenon leads to coexistence of phages and bacteria within the host. Furthermore, we highlighted that these modifications could in part impair Salmonella’s ability to colonize the gut. Overall, our findings suggest that phage-induced evolutionary pressure may be harnessed not only to control bacterial populations but also to attenuate their pathogenicity. Therefore, bacterial resistance what is often view as a limitation of phage therapy may be leveraged as a functional advantage in phage cocktail design.